Nitric oxide proxies and ocular perfusion pressure in primary open angle glaucoma. Issue 6 (17th May 2004) - Galassi, F; Renieri, G; Sodi, A; Ucci, F; Vannozzi, L; Masini, E
Abstract : Background: To investigate the levels of nitric oxide (NO) markers in plasma and aqueous humour of patients with primary open angle glaucoma (POAG) and their relation to ocular perfusion pressure. Methods: Cyclic guanosine monophosphate (cGMP) and nitrite (NO2 − ) were determined in plasma and aqueous humour of 38 patients with POAG and 46 controls. Blood pressure and IOP were measured to calculate ocular perfusion pressure (PP). Results: cGMP and NO2 − plasma levels were significantly decreased in glaucoma patients compared with controls (p = 0.001 v p = 0.004). In the aqueous humour of subjects with POAG, cGMP and NO2 − concentrations were also lower than in normal eyes (p = 0.0001 v p = 0.001). There was a linear association between cGMP in plasma and aqueous humour in glaucomas and controls ( r  = 0.514, p = 0.029 and r  = 0.558, p = 0.004) and this relation differed in the two groups (p = 0.003). Considering glaucoma patients with controls, a positive correlation was found between cGMP and PP ( r  = 0.379, p = 0.01) and between NO2 − and PP ( r  = 0.339, p = 0.040). The cGMP/PP correlation was of borderline statistical significance in controls (p = 0.050), whereas it did not attain statistical significance in POAG, as well as the association between NO2 − and PP when glaucomas and controls were considered separately. Conclusions: The authors found alterations of NO markers in the plasma and aqueous humour of glaucoma patients. Primary or secondary impaired NO balance could alter ocular perfusion pressure.